Personal Boundaries in Qualitative Research –the Delicate Matter of Contact with the Interlocutorwhen the Interview Turns into a Crisis Intervention or Therapy Session - Kuryś-Szyncel, Karolina; Mazurek, Emilia (Qualitative Research in Andragogy: Polish Research Experiences, 2026)
The chapter is a discussion on the category of personal boundaries, rarely undertakenin the research context. A research conversation (interview) was treated as a type ofmeeting, i.e. an interpersonal relationship between the researcher and the interlocutor. Theauthors point to possible crossings of personal boundaries and their effects. The article containsreconstructions of two research projects, within which the decisions made at individualstages of the research process were thoroughly analyzed. They provide a background forreproducing numerous research dilemmas, with regard to the type of relationship betweenthe study participants (interlocutors) and the researchers, that the authors had to face.